Nutrition and Diet in Maternal Diabetes An Evidence-Based Approach (Nutrition and Health, 2018)
This comprehensive volume covers all aspects of nutrition in different scenarios of maternal diabetes, including the Type 1 or Type 2 diabetic mother, gestational diabetes, and postpartum diabetes. The volumes offer a comprehensive, yet thorough, overview of the subject, from the prevalence, risk factors, and insulin requirements of the mother; to possible outcomes and effects on the infant; to dietary advice in general and specific scenarios; and information on macro and micronutrient supplements. There is also a special section on international perspectives on maternal diabetes, with ten chapters that each focus on a different country. Nutrition and Diet in Maternal Diabetes: An Evidence-Based Approach offers an overview of the Type 1 and type 2 diabetic mother, maternal and offspring aspects of gestation diabetes, and breastfeeding and maternal gestational diabetes.